2015
DOI: 10.1083/jcb.201412109
|View full text |Cite
|
Sign up to set email alerts
|

TPX2 phosphorylation maintains metaphase spindle length by regulating microtubule flux

Abstract: TPX2 is phosphorylated by Aurora A and is essential for normal microtubule flux on the metaphase spindle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 44 publications
(74 reference statements)
0
53
0
Order By: Relevance
“…The role of TPX2 in spindle assembly and size control is more complicated. Depletion of the TPX2 ortholog D‐TPX2 from Drosophila melanogaster syncytial embryos and S2 cells resulted in spindle shortening (Goshima, ; Hayward & Wakefield, ), and human cells require phosphorylation of TPX2 by Aurora A for normal spindle length (Bird & Hyman, ; Fu et al, ). In contrast, addition of recombinant TPX2 to X. laevis extracts decreased spindle length (Helmke & Heald, ), and we have observed similar effects on X. borealis spindles (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of TPX2 in spindle assembly and size control is more complicated. Depletion of the TPX2 ortholog D‐TPX2 from Drosophila melanogaster syncytial embryos and S2 cells resulted in spindle shortening (Goshima, ; Hayward & Wakefield, ), and human cells require phosphorylation of TPX2 by Aurora A for normal spindle length (Bird & Hyman, ; Fu et al, ). In contrast, addition of recombinant TPX2 to X. laevis extracts decreased spindle length (Helmke & Heald, ), and we have observed similar effects on X. borealis spindles (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…TPX2 also regulates microtubule nucleation in the spindle (Alfaro‐Aco, Thawani, & Petry, ; Petry, ; Petry, Groen, Ishihara, Mitchison, & Vale, ; Scrofani, Sardon, Meunier, & Vernos, ). TPX2 has thus emerged as a central player of spindle assembly and organization in a wide variety of cell types (Fu et al, ; Helmke, Heald, & Wilbur, ; Levy & Heald, ; Ma, Titus, Gable, Ross, & Wadsworth, ) and is overexpressed in many cancers (Chang et al, ; Neumayer, Belzil, Gruss, & Nguyen, ). Our results highlight the importance of TPX2 levels and localization as determinants of meiotic spindle microtubule architecture.…”
Section: Resultsmentioning
confidence: 99%
“…Especially AURKA, TPX2 and DLGAP5 were found to be highly upregulated and correlated with each other. It was shown that during the cell cycle TPX2 and DLGAP5 are phosphorylated by AURKA (15,35). Therefore, a coexpression of AURKA with TPX2 and DLGAP5 seems reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…E The percentage of spindle poles with n centrioles found in cells with multiple c-tubulin foci was assessed (411-805 poles were counted in each group). The significance of TPX2 in mitotic spindle formation, which relies on its interactions with Aurora-A, Eg5, Myo10, and CLASP1, has been extensively studied [22][23][24][25]48]. TPX2 is important for both spindle assembly and spindle pole integrity [16][17][18][19], but the mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%